Formation of different promoted metallic phases in PtFe and PtSn catalysts supported on carbonaceous materials used for selective hydrogenation - Stassi, Julieta Paola (2013)
In this paper, a study on the selective hydrogenation of α,β-unsaturated aldehydes to unsaturated alcohols (UA) by using two series of PtSn and PtFe catalysts with different metallic loadings and supported on carbon nanotubes and carbon Vulcan is reported. The catalysts were prepared by conventional impregnation using the corresponding metallic precursors, H 2PtCl6, SnCl2, and FeCl3. Once reduced under hydrogen flow, the supported catalysts were characterized by temperature-programmed reduction (TPR), H2 chemisorption, test reactions of the metallic phase, and X-ray photoelectron spectroscopy (XPS). Hydrogenation results show that the addition of a second metal to Pt leads to important modification of the selectivity, although the highest selectivities to UA are reached with very different Fe or Sn loadings. The performance of the catalysts in the citral hydrogenation was related to the characteristics of the bimetallic phase. It was found that the Fe addition to Pt catalysts results in a typical behavior such as for an usual ionic promoter in contact with the active metal, reaching high selectivities to UA as the Fe loading and the Fe ionic species percentage increases, while for PtSn catalysts, a high selectivity to UA was found only with a very low amount of Sn ionic species in contact with a very high percentage of Sn reduced species. The best selectivity to UA (about 98%) was found for PtSn(1wt%)/CN-P catalyst treated with N2 at high temperature.